Implementation of an evidenced based nutrition support pathway for haematopoietic progenitor cell transplant patients. Issue 3 (June 2015) - Andersen, Sarah; Brown, Teresa; Kennedy, Glen; Banks, Merrilyn
Summary Background and aims The type of nutrition support given during haematopoietic progenitor cell transplantation (HPCT) varies greatly between transplant units and often includes enteral nutrition (EN) and/or parenteral nutrition (PN). The aims of this study were to develop an evidenced based nutrition support pathway for HPCT patients and then evaluate changes in nutrition support practices post implementation of the pathway into clinical practice. Methods A retrospective audit of 66 consecutive patients who underwent HPCT during the six months prior to the development of the pathway was undertaken, followed by a prospective audit of 61 consecutive patients undertaking HPCT during the six months post implementation. Data collected included type and timing of nutrition support given. Results Post implementation of the pathway the use of PN for allogeneic HPCT patients reduced significantly from 86% to 50% (p < 0.001) and use of oral nutrition support increased significantly from 14% to 45% (p = 0.003). Autologous HPCT recipients had shorter lengths of inadequate intake with only 30% of patients having a poor intake for greater than one week compared to 72% prior to implementation of the pathway (p = 0.02). Conclusion Implementation of a nutrition support pathway impacts significantly on appropriate use of nutritional support in recipients of HPCT.